Corrosion Characteristics of Carbon Steel upon Exposure to Biodiesel Synthesized from Used Frying Oil - Adhi Setiawan; Nora Amelia Novitrie; Agung Nugroho; W Widiyastuti (Dept. of Chemical Engineering, Diponegoro University, 2017)
The use of biodiesel leads to corrosion of automotive material, which can potentially shorten engine lifetime. The study aims to investigate the effect of temperature and contact time on the corrosion characteristics of carbon steel upon exposure to biodiesel synthesized from used frying oil. The corrosion rate of carbon steel was analyzed based on weight loss measurement according to the standard of ASTM G31 as affected by temperature and contact time. The immersion temperatures used in this study were 30oC, 40oC, and 70o, respectively. The contact times studied were 30 days, 40 days, and 50 days respectively. The results show that the increase of temperature and contact time of biodiesel on carbon steel surface speeds up the corrosion rate. Maximum corrosion rate (0.083 mmy) was observed on the carbon steel contacted to biodiesel at 70oC for 50 days. The SEM results showed an irregular shape of the corroded carbon steel surface. XRD / FTIR analysis of carbon steel samples show the presence of peaks, detected as Fe2O3, FeO(OH) and Fe2O2CO3, as the corrosion products. Keywords: biodiesel; carbon steel; corrosion; FAME; used frying oil